Accessory liability in equity: the case for unconscionability. Issue 2 (7th December 2018) - Walton, Adam
Abstract: An article examining whether, amidst the huge transformation accessory liability has undergone over the past 25 years, dishonesty has been correctly identified as the touchstone of liability. Tracing the development, doctrinal underpinnings, and how the law is applied in practice, this article makes the case that unconscionability, not dishonesty, is the most appropriate touchstone for accessory liability in equity.